2015
DOI: 10.1002/qua.24914
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical insight of nitric oxide adsorption on neutral and charged Pdn (n = 1–5) clusters

Abstract: Density functional theory (DFT) calculations within the framework of generalized gradient approximation have been used to systematically investigate the adsorption of nitric oxide (NO) molecule on neutral, cationic, and anionic Pd n (n 5 1-5) clusters. NO coordinate to one Pd atom of the cluster by the end-on mode, where the tilted end-on structure is more favorable due to the additional electron in the p* orbital. On the contrary, in the neutral and cationic Pd 2 system, NO coordinates to the bridge site of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Previous studies reported that the NO adsorption process happens with charge back-donation from the Pd 4 cluster to the NO molecule. 21 Our results indicate that the amount of charge transferred between the two moieties depends on the adsorption site, but not on the arrangement. In both arrangements, adsorption in the atop mode, where back-donation to the 2π* orbital of NO seems to be less efficient, results in charge transfer from the NO molecule to the Pd 4 cluster, while for adsorption in the bridge and hollow modes, charge is transferred from the Pd 4 cluster to the NO molecule.…”
Section: Adsorption Of No On Pd 4 Clustersmentioning
confidence: 62%
See 3 more Smart Citations
“…Previous studies reported that the NO adsorption process happens with charge back-donation from the Pd 4 cluster to the NO molecule. 21 Our results indicate that the amount of charge transferred between the two moieties depends on the adsorption site, but not on the arrangement. In both arrangements, adsorption in the atop mode, where back-donation to the 2π* orbital of NO seems to be less efficient, results in charge transfer from the NO molecule to the Pd 4 cluster, while for adsorption in the bridge and hollow modes, charge is transferred from the Pd 4 cluster to the NO molecule.…”
Section: Adsorption Of No On Pd 4 Clustersmentioning
confidence: 62%
“…Recent studies proposed adsorption either on the atop 21 or on the hollow and bridge sites, 46 following previous computational studies that also suggested threefold hollow 47 or threefold hollow plus atop sites as the preferential adsorption mode. 48 In the present study, we computed the adsorption of NO on three different Pd 4 clusters, planar (Figure 1b), tetrahedral ( Figure 1c) and the distorted cluster obtained after optimization of Pd 4 over the γ-alumina surface (Figures 1f and 1g).…”
Section: Adsorption Of No On Pd 4 Clustersmentioning
confidence: 93%
See 2 more Smart Citations
“…Periodic DFT calculations, combined with ab initio thermodynamics analysis, were used to figure a phase diagram to predict plausible Pd species at relevant partial pressures and temperatures. 59,60 The following equilibrium reaction was considered (eq 2): 62,63 The structural information (CONTCAR files) of all the considered structures can be found in the SI. Note that the simulated XANES spectrum for the optimized Z[Pd] structure is similar to the experimental one for Pd imp /CHA(H 2 _NO) (Figure S5), confirming that our model is reasonable as Pd 2+ cations in CHA zeolites.…”
Section: Jacs Au Pubsacsorg/jacsau Articlementioning
confidence: 99%